2019
DOI: 10.14814/phy2.14299
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of branched‐chain aminotransferase 2 (BCAT2) enzyme impairs myoblast survival and myotube formation

Abstract: Much is known about the positive effects of branched‐chain amino acids (BCAA) in regulating muscle protein metabolism. Comparatively much less is known about the effects of these amino acids and their metabolites in regulating myotube formation. Using cultured myoblasts, we showed that although leucine is required for myotube formation, this requirement is easily met by α‐ketoisocaproic acid, the ketoacid of leucine. We then demonstrated increases in the expression of the first two enzymes in the catabolism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…It would be interesting to see the effects of muscle specific deletion of BCAT2 on skeletal muscle and whole-body metabolism. Interestingly, myoblasts depleted of BCAT2 are impaired in their ability to form myotubes ( Dhanani et al, 2019 ).…”
Section: Bcat2 and Its Regulation In Skeletal Musclementioning
confidence: 99%
“…It would be interesting to see the effects of muscle specific deletion of BCAT2 on skeletal muscle and whole-body metabolism. Interestingly, myoblasts depleted of BCAT2 are impaired in their ability to form myotubes ( Dhanani et al, 2019 ).…”
Section: Bcat2 and Its Regulation In Skeletal Musclementioning
confidence: 99%
“…ACSBG1 involves in S1P metabolism, which functions as a bioactive lipid molecule [ 26 ]. BCAT2 plays an important role in the production of the branched-chain amino acids; the study showed that the depletion of BCAT2 enzyme impairs myoblast survival, indicating a suppressing apoptosis property of BCAT2 [ 27 ]. Isotretinoin induced downregulated expression of ACSBG1 and BCAT2 might be related to decreased sebum production and apoptosis of sebocytes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This dimer catalyzes the rst step in the production of branched-chain amino acids, such as leucine, isoleucine and valine. The abnormal expression of BCAT2 also affects cell proliferation and differentiation [73]. ASNS-encoded proteins are involved in the synthesis of asparagine [74].…”
Section: Discussionmentioning
confidence: 99%